PERAN KOMUNITAS PEREMPUAN PEJUANG DALAM MENDAMPINGI KASUS KEKERASAN TERHADAP ANAK DI KELURAHAN KURAO PAGANG, KECAMATAN NANGGALO, KOTA PADANG - Irma Susanti (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The womens Fighting Community is a non-governmental organization assisted by the WCC Nurani Perempuan which is anganged in assisting cases of violonce against children (KTA), cases of domestic violonce (KDRT), and sexual violence (KS). This study aims to describe the role pf the Womens Fighting community cases of violence against children in Kurao Pagang Village, Nanggalo District, Padang City. This study uses Theory of Structural Functionalism. This research is a descriptive qualitative type. The informants of this research were the women fighters community board, the head of the Kurao Pagang Village RT, and the reporters of violence cases. The selection of informants used purposive sampling technique with 8 informants. The types of data used in this study are primary data and secondary data. The data collection methods used were in-depth interviews and document studies. The techniques used in data analysis are data collection, data processing, and descriptive analysis of the data in order to obtain in-depth information about what constitutes research. The result of this study indicate that the types of cases assisted by the Womens Fighters community and the role of the Womens Fighters community in assisting cases of violence against 2018-2019 are 1.) Cases of physical violence. 2.) Cases of physical and sexual violence assisted by the Womens Fighters community. The role of the women combatants in assisting cases of violence againts hildren, namely as a companion to cases of violence, counseling victims, collaborating with other instituons, and providing reinvorcement to victims and victims families.